(3eNJUQ ef cJGH GdUhGYb GdeQSdI Ydi GdLgejI hGdeYWdIs - (3eMeO GdehUdjs; (3GHf bje GdLhRjI , eMeO Hf CHj HcQ Hf GjhH Hf SYO GdRQYj GdOeTbj, TeS GdOjf CHh YHO Gddg,J (B751 (3g` s ((3eMeO Hf YKeGf Hf eMeO Hf SdeGf GdRQYi GdOeTbi s)
(3ChdgG (B:s
(3CeG HYO agPG ESJYLGd GdUhGYb GdeQSdI Ydi GdLgejI hGdeYWdI EfJNHJg ef cdGe TjN GdESdGe Hf bje GdLhRjI QMeg Gddg EYde Cf Gddg JYGdi HYK QShdg eMeO Udi Gddg Ydjg hSde hCgd GdCQV CMhL Edi QSGdJg ef ZjK GdSeGA s
(3BNQgG (B:s
(3hbGd JYGdi bd gde TgOGce GdPjf jTgOhf Cf Gddg MQe gPG aEf TgOhG adGJTgO eYge hTgGOJge ENHGQge Cf Gddg JYGdi MQeg hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG MhGTi HNW CMeO Hf eMeO aGWi GdPi bQCg eQJjf ceG UQM HPdc ai BNQ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds